The Psychological Impact of Coronavirus Pandemic Restrictions in Italy. The Mediating Role of the Fear of COVID-19 in the Relationship between Positive and Negative Affect with Positive and Negative Outcomes - Andrea Zammitti; Chiara Imbrogliera; Angela Russo; Rita Zarbo; Paola Magnano (MDPI AG, 2021)
Italy was quickly hit hard by the coronavirus. 'Lockdown' has significantly impacted the psychological health, personal wellbeing and quality of life of the people. The study aims to explore the relationship between positive and negative affect, as well as positive (spiritual well-being and flourishing) and negative outcomes (psychological distress caused by a traumatic life event in terms of perception of PTSD symptoms) on Italian adults during the lockdown period. Data was collected between April and May 2020. The participants were 281 Italian adults aged between 18 and 73 years. The survey was composed of the following measures: Flourishing Scale, Jarel Spiritual Well-Being scale, Positive and Negative Affect Schedule, Impact of Event Scale-Revised, Fear of COVID-19. The mediational analysis shows that fear of COVID-19 fully mediates the relationship between negative affect and spiritual well-being and flourishing; fear of COVID-19 partially mediates the relationship between negative affect and PTSD symptoms; the positive affect shows only direct effects on positive outcomes. Therefore, fear of COVID-19 does not play any mediation role. Implications for psychological interventions and future research will be discussed.